EMPLOYEE BENEFITS CUSTOMIZATION - MAJUONG KULANG MAKENY (UCU, 2024)
This dissertation explores the impact of personalization of employee benefits on job satisfaction within organizations. Organizations today operate in a business environment where the realization is increasingly dawning that benefits are going to be of paramount importance in the specific organizations that will attract, retain, and motivate talent. For sure, the one-size-fits-all benefit package of yore perhaps might not meet the diverse needs of a multigenerational workforce leading to disengagement and dissatisfaction. It aims to establish whether tailoring employee benefits to individual employees' preferences can positively impact job satisfaction, employee retention, and performance at the organizational level. The study pursues a mixed-methods approach: quantitative surveys and qualitative interviews cascade up and down the different levels of the organization in an attempt to deduce the perception of employees about their benefits and, in turn, their jobs. Analyses will be done based on demographic groups, such as age, gender, and job role, to understand if the tailored benefits have a differential impact based on employee characteristics. Results show that customized benefits have a great deal of association with the increase in job satisfaction. Employees who feel their benefits are customized are very loyal, involved, and motivated in their work. More importantly, the study determined what aspects of benefit customization employees valued the most, which involved flexible work arrangement options, healthcare, retirement, and wellness programs. Human resource management that indicates customization of benefits as one strategic tool that may be considered to better employees' levels of satisfaction. It further makes practical recommendations for organizations to enhance their human resource practices by calling on organizations to adopt a more individualistic approach to benefits that is in tandem with the diverse needs of the modern workforce.